Long-term study on coarse mode aerosols in the Amazon rain forest with the frequent intrusion of Saharan dust plumes - Morán-Zuloaga, Daniel; Ditas, Florian; Walter, David; Saturno, Jorge; Brito, Joel F.; Carbone, Samara; Chi, Xuguang; Hrab? de Angelis, Isabella; Baars, Holger; H M Godoi, Ricardo; Heese, Birgit; Holanda, Bruna A.; et al. (Atmospheric Chemistry and Physics, 2018)
In the Amazonian atmosphere, the aerosol coarse mode comprises a complex, diverse, and variable mixture of bioaerosols emitted from the rain forest ecosystem, long-range transported Saharan dust (we use Sahara as shorthand for the dust source regions in Africa north of the Equator), marine aerosols from the Atlantic Ocean, and coarse smoke particles from deforestation fires. For the rain forest, the coarse mode particles are of significance with respect to biogeochemical and hydrological cycling, as well as ecology and biogeography. However, knowledge on the physicochemical and biological properties as well as the ecological role of the Amazonian coarse mode is still sparse. This study presents results from multi-year coarse mode measurements at the remote Amazon Tall Tower Observatory (ATTO) site. It combines online aerosol observations, selected remote sensing and modeling results, as well as dedicated coarse mode sampling and analysis. The focal points of this study are a systematic characterization of aerosol coarse mode abundance and properties in the Amazonian atmosphere as well as a detailed analysis of the frequent, pulse-wise intrusion of African long-range transport (LRT) aerosols (comprising Saharan dust and African biomass burning smoke) into the Amazon Basin.
We find that, on a multi-year time scale, the Amazonian coarse mode maintains remarkably constant concentration levels (with 0.4 cmĝ'3 and 4.0 μg mĝ'3 in the wet vs. 1.2 cmĝ'3 and 6.5 μg mĝ'3 in the dry season) with rather weak seasonality (in terms of abundance and size spectrum), which is in stark contrast to the pronounced biomass burning-driven seasonality of the submicron aerosol population and related parameters. For most of the time, bioaerosol particles from the forest biome account for a major fraction of the coarse mode background population. However, from December to April there are episodic intrusions of African LRT aerosols, comprising Saharan dust, sea salt particles from the transatlantic passage, and African biomass burning smoke. Remarkably, during the core period of this LRT season (i.e., February-March), the presence of LRT influence, occurring as a sequence of pulse-like plumes, appears to be the norm rather than an exception. The LRT pulses increase the coarse mode concentrations drastically (up to 100 μg mĝ'3) and alter the coarse mode composition as well as its size spectrum. Efficient transport of the LRT plumes into the Amazon Basin takes place in response to specific mesoscale circulation patterns in combination with the episodic absence of rain-related aerosol scavenging en route. Based on a modeling study, we estimated a dust deposition flux of 5-10 kg haĝ'1 aĝ'1 in the region of the ATTO site. Furthermore, a chemical analysis quantified the substantial increase of crustal and sea salt elements under LRT conditions in comparison to the background coarse mode composition. With these results, we estimated the deposition fluxes of various elements that are considered as nutrients for the rain forest ecosystem. These estimates range from few g haĝ'1 aĝ'1 up to several hundreds of g haĝ'1 aĝ'1 in the ATTO region.
The long-term data presented here provide a statistically solid basis for future studies of the manifold aspects of the dynamic coarse mode aerosol cycling in the Amazon. Thus, it may help to understand its biogeochemical relevance in this ecosystem as well as to evaluate to what extent anthropogenic influences have altered the coarse mode cycling already.
. © 2018 Copernicus GmbH. All rights reserved.
Keywords: Aerosol; Anthropogenic Effect; Atmospheric Plume; Biogeochemistry; Biomass-burning; Dust; Long Range Transport; Rainforest; Amazon Basin; Sahara